A Study on Impact of Pharmacist Interventions on Therapeutic Outcomes of Type II Diabetic Patients in a Tertiary Care Teaching Hospital - Kumar, Voleti Vijaya; Reddy, Ankala Hemanth; Sudharshan, Jinkala; Lokendranath, Gudemella; Ugandar, RE; Chett, Challa Madhusudhana (Indian Journal of Pharmacy Practice)
Background: The management of type II diabetes mellitus is a complex, which requires continuous medical care by the health care professionals and good self-care efforts by patients. Pharmacist interventions programs delivered by the pharmacists are known to help the patients with diabetes benefited in achieving treatment goals, improving outcomes. Objectives: To study the impact of pharmacist interventions on therapeutic outcomes, determined by hemoglobin A1c (HbA1c) and secondarily on blood glucose levels, blood pressure, medication adherence, self-care activities and health related quality of life. Materials and Methods: A Prospective randomized controlled study is conducted with 150 type II diabetic patients. Of those, 75 patients were in intervention group received the pharmacist interventions over a period of 4 months and 75 patients were in control group, whereas control group do not receive interventions. The primary outcome measure was change in HbA1c and secondary outcomes were changes in fasting blood glucose, blood pressure, medication adherence, self-care activities and health related quality of life. Results: A population of 150 patients completed the study. The intervention patients exhibited a significant reduction in HbA1c values than the control group, the intervention group showed a greater reduction in the fasting blood glucose and blood pressure levels between baseline and end of the 4 months than the control group. Improvements were observed in Quality of life, self-reported medication adherence, self-care activities in the intervention group. Conclusion: A pharmacist interventions program resulted in better glycemic control, quality of life, medication adherence and self-care of type II diabetic patients over a 4-month period.
Keywords: Type II Diabetes; Pharmacist interventions; HbA1c; Quality of life; Adherence.